Compliance with Screening and Treatment of Latent Tuberculosis among Health Care Workers in a Lebanese Hospital - Farah, Stephanie; Rizk, Youssef; Khazen, Georges; Sakr, Rania (International Journal of Innovative Research in Medical Science, 2021)
Background: Health care workers (HCWs) are at increased risk of Tuberculosis infection. Various Guidelines recommend pre-placement, post-exposure, and annual screening for latent tuberculosis among HCWs. Aim: to assess the compliance of HCWs with these protocols. In addition, the study aimed to evaluate the compliance with treatment of Latent Tuberculosis and reasons of non-adherence. Methods: Study was conducted on 560 HCWs in a Lebanese hospital. A Questionnaire col-lected data on knowledge about latent tuberculosis, post-exposure screening and the reasons behind non adherence to treatment. A retrospective chart review on the same HCWs revealed data regarding TST pre-employment status, compliance to screening, seroconversion and compliance to treatment. Results: 69% of HCWs did not attend a lecture on Tuberculosis. 76% were aware of screen-ing policies. 88% performed pre-placement testing. 29% were screened post exposure. Only 4.3% had their PPD done annually. 8 HCWs seroconverted; Only 59% of positive employees initiated treatment. . Reasons included refusal or belief of no treatment benefit (55%), not being prescribed a treatment (33%), Contraindications (8%), and being afraid of side effects (4%). 15% of those who received treatment were not able to complete the full course mainly due to side effects (80%). Conclusion: We reported acceptable rates of pre-placement screening, low rates of annual screening and post exposure screening. We also reported fair rates of initiation and comple-tion of LTBI treatment. We recommend an administrative initiative to strongly implement the policies of screening for LTBI.